2015
DOI: 10.1155/2015/358125
|View full text |Cite
|
Sign up to set email alerts
|

Novel Candidate Key Drivers in the Integrative Network of Genes, MicroRNAs, Methylations, and Copy Number Variations in Squamous Cell Lung Carcinoma

Abstract: The mechanisms of lung cancer are highly complex. Not only mRNA gene expression but also microRNAs, DNA methylation, and copy number variation (CNV) play roles in tumorigenesis. It is difficult to incorporate so much information into a single model that can comprehensively reflect all these lung cancer mechanisms. In this study, we analyzed the 129 TCGA (The Cancer Genome Atlas) squamous cell lung carcinoma samples with gene expression, microRNA expression, DNA methylation, and CNV data. First, we used varianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 124 publications
1
21
0
Order By: Relevance
“…The methylation status of HOXD3, ARHGDIB, AGAP2 genes was reported to be involved in cell signaling and cytoskeletal organization in squamous cell lung carcinoma. Furthermore, the methylation status of these genes predicted the prognosis of patients (91).…”
Section: Epigenomicsmentioning
confidence: 99%
“…The methylation status of HOXD3, ARHGDIB, AGAP2 genes was reported to be involved in cell signaling and cytoskeletal organization in squamous cell lung carcinoma. Furthermore, the methylation status of these genes predicted the prognosis of patients (91).…”
Section: Epigenomicsmentioning
confidence: 99%
“…[49] Another study evaluated a wide range of novel cancer drivers for LUSC and found that patients with high expression of the ARHGDIB gene had good prognoses while patients with high expression of the HOXD3 gene had poor prognoses. [50] Another paper studied whether the addition of multiple genomic components to existing prognostic models for LUSC improved predictive powers and found no significant improvement, suggesting that measurements at the transcription level may be more predictive of clinical outcomes than measurements at the DNA\ epigenetic level for LUSC. [51]…”
Section: Additional Research Based On Tcga Lung Cancer Data Setsmentioning
confidence: 99%
“…We found that approximately 1.3% of the predicted miRNA targets formed reciprocal "up-down" or "down-up" expression relationships with miRNAs, suggesting that the modulation of miRNA-mRNA interactions could be promising biomarkers for cancers. Integrated expression analysis of miRNAs and mRNAs using microarray technology have revealed signatures implicated in ovarian cancer [165,166] , breast cancer [167][168][169][170][171] , metastatic osteosarcoma [172] , gastric cancer [173,174] , pancreatic cancer [175] , oral squamous cell carcinoma [176] , lung cancer [177][178][179] , prostate cancer [180,181] , follicular thyroid tumors [182] , retinoblastoma [183] , etc. The miRNA/mRNA interactome not only includes the interactions between an miRNA and its targets but also comprises the TF-miRNA network.…”
Section: Integrated Analysis Of Mirnas and Mrnas In Cancermentioning
confidence: 99%